A tale of two countries – forty years on: politics and teacher education in Russia and England. Issue 5 (20th October 2017) - Menter, Ian; Valeeva, Roza; Kalimullin, Aydar
Abstract: The relationships between politics and teacher education have become increasingly close over recent decades in many contexts around the world, often causing significant challenges as well as some opportunities. In this article, we draw on a project on the reform of teacher education in Russia and through a comparison with the development of teacher education policy in England – especially over the last forty years – we explore how the evolution of a new politics in both contexts has affected policy on teaching and teacher education. Looking, for example, at 'post-communism' and 'neoliberalism' and their respective impacts on political systems, a number of contradictions and paradoxes are identified, when comparisons are drawn between the two systems.